INQUIRY-BASED, LEARNING-BASED LKPD TO IMPROVE STUDENTS' INTERPERSONAL INTELLIGENCE - Algae Arine Fristya Yuniar; Sri Wardani; Sudarmin Sudarmin; Sri Haryani (Sean Institute, 2023)
The purpose of this research is to enhance students' interpersonal intelligence via the participation in school-based learning dialogues, practicums, and presentations. Through in-depth interviews, direct observation, and the analysis of documents pertaining to the process of witnessing student participation, this research approach is descriptive qualitative. (interpersonal). The level of participation of students during class discussions, as well as the abilities of students to build Inquiry Learning-based LKPD and interpersonal intelligence during practical experiences, are the primary foci of this study. Following the collection of data, it is subjected to analysis, verification, and the formation of scientific knowledge that may be used as a teaching tool in educational institutions. When utilising worksheets that are based on inquiry learning, the outcomes and conclusions on one's interpersonal intelligence improve with a higher average..